Rancang Bangun Alat Informasi Penjemputan Siswa Berbasis Mikrokontroller ESP32 - Maulana, Irfan; Bachtiar, Moh. Muaz; Fadlun, Wira; Sakti, Fredi Prima (Jurnal Sistem Komputer dan Informatika (JSON), 2024)
In daily life, the phenomenon of traffic density increases significantly during school hours. There are many ways to overcome this phenomenon, one of which is making a student pickup information tool based on the ESP32 microcontroller. The tool created is in the form of a student pick-up information display, which will display the student's name and class when the parent has correctly entered the code via the web application. Student pickup information tools use hardware and software. The hardware consists of an ESP32 microcontroller as a manager for input data and output data which is the link between the web server and the P10 LED display and the P10 DMD panel to display the name and class data of the students being picked up. Meanwhile, the software uses Arduino IDE software and MySQL database. The results of testing from a series of research shows efficiency and activeness in picking up students with a success percentage of 100% with testing 15 times.